Abertura de empresas no estado do Pará: análise dos impactos da substituição da eireli pela slu a partir da lei de liberdade econômica - XAVIER FILHO, Uender Soares (2023)
The study envisages carrying out, through a comparative analysis focusing on two business institutes (EIRELI and SLU), the impacts of replacing the fist to the detriment of the other. The exam seeks to understand how SLU influenced the movement to start a business, in a case study in the business reality of the State of Pará. The question is: in what way, considering the context of the Economic Freedom Law, did the SLU influence the movement of commercial registration in the State of Pará, in view of the comparative analysis in relation to the EIRELI? Thus, a data collection was carried out in JUCEPA. The data collected comprise the number of companies opened by business type in two periods. The first one was between 2011 and 2013, the second, between 2019 and 2021. The fist chapter deals with the innovations arising from the Economic Freedom Law. The second analyzes the main business types present in the data survey carried out with JUCEPA. The third chapter uses data referring to the opening of companies in the State of Pará, focusing on the institutes of EIRELI and SLU, examining them in a comparative way, in the two proposed periods. In the final conclusions, it is noticeable that fostered the process of company regularization. Besides that, it is possible to state thar the SLU institute adapted to the Brazilian reality of small and medium-sized entrepreneurs, with the limited model being more suitable for entrepreneurs from Pará.